Fluoxetine Facilitates Fear Extinction Through Amygdala Endocannabinoids - Gunduz-Cinar, Ozge (Neuropsychopharmacology, 2016)
Pharmacologically elevating brain endocannabinoids (eCBs) share anxiolytic and fear extinction-facilitating properties with classical therapeutics, including the selective serotonin reuptake inhibitor, fluoxetine. There are also known functional interactions between the eCB and serotonin systems and preliminary evidence that antidepressants cause alterations in brain eCBs. However, the potential role of eCBs in mediating the facilitatory effects of fluoxetine on fear extinction has not been established. Here, to test for a possible mechanistic contribution of eCBs to fluoxetine's proextinction effects, we integrated biochemical, electrophysiological, pharmacological, and behavioral techniques, using the extinction-impaired 129S1/Sv1mJ mouse strain. Chronic fluoxetine treatment produced a significant and selective increase in levels of anandamide in the BLA, and an associated decrease in activity of the anandamide-catabolizing enzyme, fatty acid amide hydrolase. Slice electrophysiological recordings showed that fluoxetine-induced increases in anandamide were associated with the amplification of eCB-mediated tonic constraint of inhibitory, but not excitatory, transmission in the BLA. Behaviorally, chronic fluoxetine facilitated extinction retrieval in a manner that was prevented by systemic or BLA-specific blockade of CB1 receptors. In contrast to fluoxetine, citalopram treatment did not increase BLA eCBs or facilitate extinction. Taken together, these findings reveal a novel, obligatory role for amygdala eCBs in the proextinction effects of a major pharmacotherapy for trauma- and stressor-related disorders and anxiety disorders.